The Chlamydia M278 Major Outer Membrane Peptide Encapsulated in the Poly(lactic acid)-Poly(ethylene glycol) Nanoparticulate Self-Adjuvanting Delivery System Protects Mice Against a Chlamydia muridarum Genital Tract Challenge by Stimulating Robust Systemic and Local Mucosal Immune Responses - Verma, Richa; Sahu, Rajnish; Dixit, Saurabh; Duncan, Skyla A.; Giambartolomei, Guillermo H.; Singh, Shree R.; Dennis, Vida A. (Frontiers in Immunology, 2018)
Recently, we reported that our PPM chlamydial nanovaccine [a biodegradable co-polymeric PLA-PEG (poly(lactic acid)-poly(ethylene glycol)]-encapsulated M278 peptide (derived from the major outer membrane protein (MOMP) of Chlamydia)] exploits the caveolin-mediated endocytosis pathway for endosomal processing and MHC class II presentation to immune-potentiate Chlamydia-specific CD4+ T-cell immune effector responses. In the present study, we employed the Chlamydia muridarum mouse infection model to evaluate the protective efficacy of PPM against a genital tract challenge. Our results show that mice immunized with PPM were significantly protected against a homologous genital tract challenge evidently by reduced vaginal bacterial loads. Protection of mice correlated with enhanced Chlamydia-specific adaptive immune responses predominated by IFN-γ along with CD4+ T-cells proliferation and their differentiation to CD4+ memory (CD44high CD62Lhigh) and effector (CD44high CD62Llow) T-cell phenotypes. We observed the elevation of M278- and MOMP-specific serum antibodies with high avidity in the ascending order IgG1 > IgG2b > IgG2a. A key finding was the elevated mucosal IgG1 and IgA antibody titers followed by an increase in MOMP-specific IgA after the challenge. The Th1/Th2 antibody titer ratios (IgG2a/IgG1 and IgG2b/IgG1) revealed that PPM evoked a Th2-directed response, which skewed to a Th1-dominated antibody response after the bacterial challenge of mice. In addition, PPM immune sera neutralized the infectivity of C. muridarum in McCoy cells, suggesting the triggering of functional neutralizing antibodies. Herein, we reveal for the first time that subcutaneous immunization with the self-adjuvanting biodegradable co-polymeric PPM nanovaccine immune-potentiated robust CD4+ T cell-mediated immune effector responses; a mixed Th1 and Th2 antibody response and local mucosal IgA to protect mice against a chlamydial genital tract challenge.